Study of The Calculation of The Potential Environmental Impact of Crude Oil Production on The Crude Oil and Gas Explore Industry in Sumatra Using The Life Cycle Assessment Method - Al Hanif, Ervando Tommy; Saputro, Purnomo Adi; Faadhilah, Isaaf; Sari, Masyiswa Fatika; Pertiwi, Damai Sinar; Farida, Alifah Al (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2024)
The energy or oil and gas industry is one of the largest contributing sources in Indonesia because of the high demand for oil and gas fuel. Still, it produces emissions and waste that have the potential to damage the surrounding environment. This research aims to analyze the identification of potential environmental impacts from the petroleum and natural gas industry in Sumatra using the life cycle assessment method so that it can provide recommendations for improvements in reducing environmental impacts in the petroleum and gas industry. This research uses the life cycle assessment (LCA) SNI ISO 14040:2016 concerning Life Cycle Assessment - Principles and Framework and SNI ISO 14044:2017 concerning Life Cycle Assessment - Requirements and Alloys using SIMAPRO Developer 9.4.0.2 software. The results are as follows: 1) The oil and gas industry has conducted a life cycle assessment study according to SNI ISO 14040:2016 and 14044:2017 standards, involving 100% of its petroleum products. 2) The data quality is adequate for life cycle impact assessment, with the data collected reaching 100% completeness. 3) The results of the environmental impact assessment cover 12 relevant impact categories, providing a comprehensive picture of the impacts produced by the oil and gas industry on the environment; 4) the main focus on essential issues can be directed at core processes or production within the scope of the oil and gas industry. 5) Efforts to improve the environment can be focused on the processing unit, which is an important issue, namely diesel-based generator emissions from the power plant process unit. 6) The sensitivity analysis results show that changes in emission values in the power plant process unit do not significantly affect the resulting potential impacts. Hence, this emission value is not sensitive based on the collection method. 7) Recommendations are given based on important issues that have been identified.